(untitled) (Indian Journal of Animal Production and Management, 2024)
In modern intensive farming systems, animals are always subjected to some degree of human contact. The quality of human-animal interactions has a profound impact on the productivity and welfare of farm animals. Regular pleasant contact with humans may result in desirable alterations in the physiology, behaviour, health and productivity of farm animals. In contrast, animals subjected to aversive human contact may become highly fearful of humans and their growth and reproductive performance will be compromised. An animal’s perception of humans in the presence of humans, results in frightening, neutral and pleasant emotions. A regular positive human contact or handling is a powerful and reliable method to reduce the stress and fear reactions in farm animals whereas negative handling by stockperson is negatively correlated with milk yield, protein and fat content. Human contact may cause alterations in brain physiology and morphology as the farm animals encountering challenging conditions often show some degree of immunosuppression. This paper discusses the importance of good human-animal relationship for improving animal welfare and production with special reference to dairy animals.